Building capability for in situ quantitative characterisation of the ocean water column using acoustic multibeam backscatter data. Catalyst: Seeding Activity Report - Lamarche, G; Vanessa Lucieer (2018)
The objective of this project was to enhance our ability to develop protocols and methodologies for identifying and quantifying features such as gas, oil, and freshwater in the ocean using marine acoustic technology. Such approaches are still in their infancy but since New Zealand has sovereign rights over 4,000,000 km 2 of ocean in which resources (fish, minerals, hydrocarbons) are vast but mostly unquantified, they potentially provide considerable economic, environmental and cultural benefits to New Zealand by improving our capacity to manage our marine estate. This project has established a multidisciplinary research consortium of internationally recognised experts in marine acoustics and geophysics, spatial analysis and environment, from New Zealand (NIWA, University of Auckland), France (CNRS-Géosciences Rennes, IFREMER), Australia (Institute for Marine and Antarctic Studies, University of Tasmania, Hobart, Tasmania - IMAS-UTAS), USA (University of New Hampshire, Centre for Coastal and Ocean Mapping - UNH-CCOM), Germany (GEOMAR), and Belgium (FPS Economy). During the April 2017 workshop, in Rennes, France, we reviewed the state of scientific and technological knowledge on water column data, identified key technical issues (data acquisition, use and transfer), and designed the concept of an ambitious marine geophysical survey in New Zealand required to address the key scientific questions. During year two, we finalised an ambitious multi-institute survey proposal. The project culminated in a New Zealand funded 20-day voyage of R.V. Tangaroa to which twenty participants from 8 organisations brought specific expertise and equipment. The acoustic survey focused on a large active hydrothermal vent field in the Bay of Plenty and resulted in the collection of an outstanding marine acoustic and ground truthing dataset over intensive methane and CO 2 vents. Our survey proved exceptionally successful and demonstrated the potential to differentiate methane and CO 2 bubbles in the water column. A result thought ...